Penanggulangan Prostitusi Online Menggunakan Teori Kontrol Sosial - Isnawan, Fuadi (Universitas Batanghari Jambi, 2025)
The development of information and communication technology has brought significant changes in various aspects of human life, including in the social and sexual fields. One of the phenomena that has emerged due to technological advances is online prostitution, known as “Open Booking Order” (Open BO). This research aims to examine the Open BO phenomenon in the context of Indonesian criminal law, focusing on its impact on youth morality and public safety. This research uses normative legal research methods, with a statutory approach. The results show that tackling online prostitution must be done comprehensively, involving the government, security forces, and the active participation of the community to ensure the creation of a more just, safe, and dignified environment. Especially among adolescents, countermeasures require an approach that prioritizes attachment to family and the environment, affection, positive use of leisure time, and increasing faith and piety. Attachment to family and the environment such as peers and school can create a sense of security and emotional support that reduces the risk of deviant behavior. Support from family and community strengthens attachment, while involvement in positive activities helps adolescents fill their free time with useful activities. In addition, increasing faith and piety through religious guidance strengthens moral and spiritual values, guiding adolescents to avoid actions that go against religious teachings.